Pengetahuan, Sikap Dan Perilaku Mahasiswa Terhadap Efek Penyembuhan Luka Dari Bubuk Kopi (Coffea sp.) - Desty, Rani Tiara; Waris , Muhammad Anugerah Alam; Putri , Rolita Ramadani (Universitas Borneo Lestari, 2025)
Coffee grounds (Coffea sp.) is a traditional medicine that can be used to heal wounds. This coffee powder contains alkoloids, flavonoids, tannins, steroids, saponins, phenols, caffeine and chlorogenic acid. Based on preliminary studies, there are still many students who do not know the benefits of coffee for healing wounds. The aim of this research is to determine the knowledge, attitudes and behavior of students regarding the wound healing effects of coffee grounds (Coffea sp.). The type of research used is quantitative descriptive with a cross-sectional approach. The sampling method in this research uses probability sampling with disproportionate stratified random sampling technique as the sample determination technique. The subjects of this research were 147 midwifery students from the Surakarta Ministry of Health Polytechnic. The results of the research showed that students in the Diploma III Midwifery Study Program, Poltekkes Kemenkes Surakarta, had a level of insufficient knowledge, namely 60.5%, sufficient attitude, namely 72.1%, and inadequate behavior, namely 81.6% regarding the effect of coffee on wound healing. It is hoped that there will be further research related to providing counseling on coffee for wound healing to midwifery students.